Армения-Казахстан: 25 лет конструктивного межгосударственного взаимодействия (Հայաստան-Ղազախստան. 25 տարվա միջպետական կառուցողական համագործակցություն) - Ադիլբաեվ Ժալգաս (YSU Journal of International Affairs, 2018)
The article analyzes the level of interstate relations between the Republic of Armenia and the Republic of Kazakhstan in the sphere of political, economic, military-technical and cultural-humanitarian cooperation. The author touches upon the prospects for further bilateral cooperation within the framework of integration associations.